Embolization of an Aberrant Right Subclavian Artery Aneurysm with Amplatzer Vascular Plug without Bypass - Leong, Chuo Ren; Solaimanzadeh, Isaac; Rosca, Mihai; Siegel, David; Giangola, Gary (International Journal of Angiology, 2012)
Aberrant right subclavian artery (ARSA) aneurysms are rare, but the risk of rupture and thromboembolism is high, with a postrupture mortality rate of 50%. Open surgical repair of ARSA aneurysms usually requires thoracotomy and aortic grafting, which can be contraindicated in high-risk patients with multiple comorbidities. Endovascular repair of ARSA aneurysms has been reported, with or without adjunctive surgical bypass. We report a case of an 80-year-old woman resenting with an asymptomatic 4 cm ARSA aneurysm who underwent a completely endovascular treatment of the aneurysm using an Amplatzer vascular plug II (St. Jude Medical Inc., St. Paul, MN).
Keywords: endovascular procedure; endovascular repair; aneurysm; artery; percutaneous; subclavian; vessel repair